Effect of compound isolated from Lawsonia inermis (L.) (Myrtales: Lythraceae) on the immature stages of filarial vector Culex quinquefasciatus Say (Diptera: Culicidae) and its docking analysis with Acetylcholinesterase (AChE1). (July 2018) - Sandhanam, Sylvester Darvin; Ganesan, Pathalam; Stalin, Antony; Michael, Gabriel Paulraj; Balakrishna, Kedike; Pandikumar, Perumal; Ignacimuthu, Savarimuthu; Naif, Abdullah Al-Dhabi
Abstract: The aim of the present study was to evaluate the mosquito larvicidal activity of lawsone isolated from Lawsonia inermis (L). The larvae were exposed to four different concentrations of lawsone (0.5, 1.0, 1.5 and 2.0 ppm). After 24 h and 120 h post treatment the larval mortality and ovicidal activity were recorded. However, Lawsone shows significant larvicidal activity against Culex quinquefasciatus with LC50 and LC90 values of 0.72 and 5.04 ppm along with 84% of ovicidal activity at 2 ppm concentration. Histopathological study revealed that serious damage on the larval midgut cells. Lawsone showed no harmful effect on the tested organism Poecilia reticulata. Lawsone was highly active and inhibited AChE in a concentration dependent manner. Lawsone presented highest inhibition against AChE extracted from Cx. quinquefasciatus with IC50 of 0.69 μg/mL. The chemical structure of lawsone was identified based on spectroscopic analysis and literature spectral data. Insect-specific cysteine residues of AChE1 inhibitors will not interact with AChE1 of other organisms. Computational analysis showed that lawsone made strong binding interaction with cysteine residue in the AChE1 of Cx. quinquefasciatus . Hence, these results suggested that lawsone might act as a mosquito specific AChE1 inhibitor. Highlights: An active compound 'Lawsone' was isolated from the leaves of Lawsonia inermis (L.). Lawsone showed good larvicidal activity against Cx. quinquefasciatus. Lawsone recorded LC50 of 0.723ppm in mosquito larvae. Lawsone heavily damaged the larval midgut cells of Cx. quinquefasciatus. Lawsone inhibited AChE activity in Cx. quinquefasciatus significantly.